Distribution pattern and population structure of Calanus australis Brodsky, 1959 over the southern Patagonian Shelf off Argentina in summer - Sabatini, Marina Elena (2000)
In the southwest Atlantic Ocean, Calanus australis is widely distributed in waters of the inner and middle shelf off Argentina. Along the coast of southern Patagonia it is the most abundant large copepod through all seasons, typically occurring at higher densities over the inner shelf < 100 m deep. Its concentration decreases offshore as it is replaced by Calanus simillimus and Neocalanus tonsus. The abundance, vertical distribution, and population structure of Calanus australis off Patagonia were examined during a summer survey (March 1998) in order to study the ecological response of the copepod to hydrographic conditions. Differences in population densities were related to geographical difference in water-column stability. Higher numbers were recorded inshore at 51°S in strongly stratified coastal waters, where a well developed thermocline was present at 50 m. A sharp decline in abundance was evident southwards, coinciding with the occurrence of highly mixed, coastal, isothermal, and isohaline waters. Very low concentrations were also found at the most offshore, thermally stratified stations influenced by transitional waters between shelf and Malvinas waters. The population consisted mainly of stage 5 copepodites and fewer adult females. The scarcity or absence of younger stages cannot be attributed to the mesh size employed (150μm). The population dynamics of Calanus australis are discussed and compared with other Calanus species. © 2000 International Council For the Exploration of the Sea.